The Impact of Modern Trends in the Social Work and Social Care in the Republic of Macedonia - Nackovska – Veljkovikj, Biljana (European Journal of Multidisciplinary Studies, 2016)
Social care is an organised network of institutional and non-institutional facilities designed to meet the needs of citizens. The reforms that are taking place in social protection are influenced by modern trends in social work, expressed through decentralization, de-institutionalization, pluralism, strengthening of civil society and the possibility of providing private services, affecting and enriching the content of social work. These change the relationship to the client’s position and improve the professionalism of social worker. Changes in social policy, resulting from diverting from central to local level, influence and give direction to the overall social activity. The paper describes the three components thereof (areas): the state of social work and social protection in the Republic of Macedonia, rights and services in the social protection system in the Republic of Macedonia and research part. Starting from the assumption that modern trends affect reforms in the social protection system of the Republic of Macedonia, this paper aims to determine the state of social protection in the Republic of Macedonia. The aim is to gain knowledge about the situation and the changes occurring in the social institutions of public character, influenced by modern trends. Also this paper makes analysis of the legislation in the Republic of Macedonia in the field of social protection. Ultimate goals of the implementation of reforms in the social protection are the welfare of the beneficiary, improving the quality of work and professional development of social workers.